Death row welcomes you: visiting hours in the shadow of the execution chamber - Hale, Steven (Melville House, 2024)
"Combining topics such as crime, death, and life inside prison, an award-winning journalist, writing with humanity, empathy and insight, and gaining unprecedented access, traces the interwoven lives of condemned prisoners and the men and women who come to Riverbend Maximum Security Institution to visit them"--